COMPARATIVE VALUE OF OHI-S INDEX BETWEEN WATER USERS OF EX-COAL MINING WATER AND TAP WATER - Widodo, Widodo; Aristia, Firda; Adhani, Rosihan (FKG Unlam, 2018)
Background: Ex-coal mining water is water that contains low pH of 4.31 and high dissolved metal concentration, such as iron (Fe) 2,335 mg/l and manganese (Mn) 10,982 mg / l. Low pH and high metal content in ex-coal mining excavation water can cause some effects if used to brush teeth for long period of time. It can cause dental disease and also affect OHI-S to turn bad. Objective: To analyze the comparison of OHI-S index values between the worker who used ex-coal mining water and tap water at PT. Rahmat Barajaya Utama. Methods and materials: This research was observational analytic study with cross-sectional approach, using simple random sampling technique, consisted of two groups. Each sample consisted of 30 workers who use excoal mining excavation water and 30 workers who use tap water. The total of 60 people as samples were examined using Green and Vermillionâs OHI-S index. Results: Result of data analysis with Mann Whitney test at p = 0,000, where Î± value was 0,05. Thus, p> Î±, ie 0,000> 0.05. Conclusion: The OHI-S index of workers who use ex-coal mining water is worse than those who use tap water at PT. Rahmat Barajaya Utama.